Factors influencing the FDI Location choice for knowledge intensive services and headquarters within the EU and Austria - Martin Falk (FIW - Research Centre International Economics, 2012)
This study investigates the determinants of bilateral Greenfield FDI projects and flows in knowledge intensive business services from OECD/BRIC countries to the EU countries for the period 2003-2010. Greenfield FDI projects are distinguished by type of activity: (i) business services, (ii) design, development and testing activities, (iii) headquarters activities and (iv) R&D services. Another aim of this study is to provide new empirical evidence on the patterns of Greenfield investments in knowledge intensive business services over time, source country and destination country. For Austria, the number of Greenfield investments in headquarter functions remains stable over time whereas Greenfield investments in R&D and related activities declined during the sample period. The same holds true for the number of jobs generated through greenfield investments. The results using panel count data models show that wage costs, tertiary education, corporate taxes, having a common border and sharing a common language all play a significant role in determining bilateral Greenfield FDI projects in knowledge intensive services. However, the impact of corporate taxation and labour costs differs widely across the functions and does not play a role in Greenfield investments in R&D and development, design and testing services.
Keywords: F23; 330; Greenfield foreign direct investment; knowledge intensive business services; headquarter functions; R&D activities; gravity equation; panel data; FDI determinants